Single piece artificial urinary sphincter for secondary incontinence following successful repair of post traumatic urethral injury - D K Kandpal; S K Rawat; S Kanwar; A Baruha; S K Chowdhary (Wolters Kluwer Medknow Publications, 2013)
Post traumatic urethral injury is uncommon in children. The management of this condition is dependent on the severity of injury. Initial suprapubic cystostomy with delayed repair is the conventional treatment. Successful reconstruction of urethral injury may be followed by urethral stricture, incontinence, impotence, and retrograde ejaculation. Successful repair of post traumatic urethral injury followed by secondary incontinence in children has not been well addressed in literature. We report the management of one such child, with satisfactory outcome with implantation of a new model of single piece artificial urinary sphincter in the bulbar urethra by perineal approach.